Critical Infrastructure Resilience and Sustainability Reader - Lewis, Ted G. (Hoboken, New Jersey: John Wiley & Sons, 2024)
"The field of homeland security has shifted since 9/11 and is now consumed by climate change threats, mainly drought, and natural disasters. Critical Infrastructure Resilience & Sustainability Reader analyzes the complex network of entities that make up the nation's infrastructure, and identifies vulnerabilities and risks in various sectors--and frames them in terms of sustainability and resilience. Written as a go-to resource for professionals in the field, this book reduces the complex problem of protecting water supplies, energy pipelines, telecommunication stations, power grid, and Internet and Web networks to a much simpler problem of protecting a few critical nodes--all without any complicated mathematical models. With clear graphics and a conversational style, the narrative guides non-technical readers through each infrastructure sector, building a basic understanding of how they work, how they are regulated, and what threats can disrupt them"-- Provided by publisher.
Keywords: Infrastructure (Economics) -- Risk Assessment